Critical considerations for immunocapture enrichment LC–MS bioanalysis of protein therapeutics and biomarkers. (4th July 2018) - Zhao, Yue; Gu, Huidong; Zheng, Naiyu; Zeng, Jianing
In recent years, immunocapture enrichment coupled with LC–MS technology has seen more applications for the measurement of low abundant protein therapeutics and biomarkers in biological matrices. In this article, several critical considerations for the application of immunocapture enrichment to LC–MS bioanalysis of protein therapeutics and biomarkers, including reagent selection, reagent characterization, designing of capture format, etc. are discussed. All these considerations are critical in developing reliable and robust bioanalytical assays with high assay specificity and sensitivity. Successful examples using the immunocapture LC–MS approach in the quantification of biotherapeutic and low abundant protein biomarkers will also be discussed.